Introduction Sections of Research Articles with High and Low Citation Indices. - Suryani, Ina; Aizan, Y.; Aziz, Noor Hashima Abd. (Pertanika Journal of Social Sciences & Humanities, 2015)
Citation index for publication is one of the sought-after criteria for university ranking and it contributes to significant merits in an academician's performance evaluation. Citation indices are systematically generated to indicate the number of times a paper is cited by other writers. As such, it is deemed to be more neutral and unprejudiced in determining the value of the research articles. In view of the importance of citation index, this study compares the strategies used in presenting research work in the introductory sections of highly cited research articles and those that have never been cited. In order to be cited, the introduction section of the research article must be able to capture the interest of readers, which includes editors, reviewers, and the research community. Otherwise, readers may choose to read or cite other articles. Given the importance and complexity of an article, the introduction section is deemed to be the most challenging section to write by many scientific writers. Therefore, this paper compares the presentation of the introduction sections of Computer Science research articles in highly cited articles and those that have never been cited. A total of 127 research articles published in Scopus-indexed journals written by academicians from Malaysian universities were analysed using move analysis. The scheme for move analysis is derived from the CARS model (Swales, 2004). Apart from promoting the findings obtained in the research work, this study also suggests that the highly cited research articles have higher percentages of strategy realisation compared to research articles that have low citation.